Developing a Culturally and Methodologically Adapted Eye Movement Desensitization and Reprocessing Therapy Protocol for Major Depressive Disorder in Pakistan - Anwar, Khan; Amalia, Madihie (Science Partner Journals, 2025)
Major depressive disorder (MDD) ranks as the 24th leading cause of disability-adjusted life years worldwide, contributing substantially to the global mental health burden. In Pakistan, socioeconomic challenges such as poverty, political instability, and inadequate mental health resources exacerbate the high prevalence of MDD. Eye movement desensitization and reprocessing (EMDR) therapy, although globally recognized as an effective evidence-based intervention for MDD, reflects Western psychological frameworks that may not align with the sociocultural realities of non-Western contexts like Pakistan. Moreover, limited empirical research exists on the cultural and methodological adaptation of EMDR therapy in Pakistan. To bridge these research gaps, this study focused on developing a culturally and methodologically adapted DeprEnd EMDR therapy protocol to suit the distinct needs of clients and therapists in Pakistan. Utilizing a qualitative exploratory research design, the study integrated insights from a narrative literature review and expert focus group discussions to identify essential adaptations across all phases of the DeprEnd EMDR therapy protocol. The findings of this study revealed several critical cultural and methodological adaptations necessary to enhance the effectiveness of the DeprEnd EMDR therapy protocol in Pakistan. Key cultural themes included integration of local languages, cultural metaphors, and religious practices; addressing stigma; involving families for support; and ensuring gender-sensitive practices. Methodological themes emphasized restructured therapy phases, use of visual assessment tools, simplified language, and adaptation for online delivery to improve accessibility and therapeutic outcomes. These adaptations align the DeprEnd EMDR therapy protocol with the collectivist, resource-limited context of Pakistan, promoting its acceptance and efficacy. To conclude, this research created a culturally and methodologically adapted DeprEnd EMDR therapy protocol specifically designed for Pakistan. The adapted protocol is scalable and holds promise for broader use in other South Asian nations with comparable cultural contexts. Therefore, by bridging global practices with local needs, this research provides a major contribution to the evolving field of culturally competent mental healthcare.